ANALISIS FRAMING MEDIA ONLINE DALAM PEMBERITAAN JOKOWI MENGANGGUK SAAT DITANYA SOAL RESHUFFLE KABINET (STUDI PADA SITUS BERITA ONLINE DETIK.COM EDISI 26 DESEMBER 2022) - Kurniawati, Dewi; Simamora, Andreas Julangdi Java (CV. Kalimasada Group, 2024)
Digitalization is a significant thing, where almost everyone got the ability to easily access various information. One of the mediums to access that information is something called online news site. Approaching the politicial year, every word and action that’s coming out from the mouth of the political figure surely interesting to be followed. This research objective is to aid people dissecting news using framing analysis through a news entitled “Jokowi Nods when Asked about Cabinet Reshuffle” in the online news site, detik.com. This research is using online observation tech in collecting data which is applicated by observing and downloading the news, then proceed with captured the screen where the news is opened. Pan and Kosicki model is the one that the researcher used. Pan and Kosicki model is an analysis approach that researcher use in this research by applicating qualitative descriptive metode. Framing's done by dessecting in detail the object of this research based on four framing structures of Pan and Kosicki model. Syntactic, script, thematic, and rhetorical are the four framing structures, although in this news graphs and tables is not available on the rhetorical structure component.